Perencanaan Strategis Pada Sistem Informasi dengan Menggunakan Metode Ward and Peppard - Brian Farrel Hermanto; Andeka Rocky Tanaamah (STMIK Budi Darma, 2021)
CV. Bumi Printing is a company that focuses on printing. Currently my CV. Bumi Printing does not yet have an accurate IS/IT infrastructure, so it does not use information system applications and information technology, which affects business development and has indirect effects that cause inefficiency. Therefore, strategic planning of information systems is carried out within the framework of Ward and Peppard. There are several analyzes and observations that must be made to properly analyze the strategic plan. Specifically for internal/external environment analysis using SWOT and IS/IT internal/external business environment analysis using IS/IT value chain. Thus, the information system application portfolio diagram using Ward and Peppard McFarlan which is expected to have a good impact, among others, inventory information systems, financial information systems, competitor inventory management information systems, and attendance information systems, emerges strategically. Bumi printing and printing can solve problems related to company data collection which is still done manually